Vitamin-mineral complexes to help adult patients frequently suffering with acute respiratory viral infections: A review - Dmitry I. Trukhan; Natalya V. Bagisheva (ZAO "Consilium Medicum", 2024)
Acute respiratory viral infections are widespread diseases, poorly controlled infections and are characterized by moderately pronounced constant growth. The use of vitamin-mineral complexes (nutraceuticals) for nonspecific prevention and treatment of acute respiratory viral infections is experiencing a "second youth" thanks to new data accumulated during the novel coronavirus infection (COVID-19) pandemic. As part of the review, we examined the possible impact of deficiency of the microelements selenium and zinc, vitamins A, E and C on various aspects of the course of ARVI: nonspecific prevention, treatment and rehabilitation. We searched for relevant sources in the PubMed and Scopus information databases, including the time period up to 04.07.2024. The presence in the arsenal of a practicing physician of 2 forms of the vitamin-mineral complex Selzinc® at the outpatient stage of medical care will increase the effectiveness of nonspecific prevention of ARVI in the pre-epidemic period, especially in "frequently ill adults with ARVI," as well as the treatment of ARVI as adjuvant therapy and subsequent rehabilitation.